Bimetallic alloy and semiconductor support synergistic interaction effects for superior electrochemical catalysis. Issue 7 (12th February 2020) - Zheng, Yunshan; Zhai, Yan; Tu, Maomao; Huang, Xinhua; Shu, Mingcong; Guo, Xiaoyu; Ying, Ye; Wu, Yiping; Wen, Ying; Yang, Haifeng
Abstract : The design and fabrication of economically viable anode catalysts for the methanol oxidation reaction (MOR) have been challenging issues in direct methanol fuel cells (DMFCs) over the decades. Abstract : The design and fabrication of economically viable anode catalysts for the methanol oxidation reaction (MOR) have been challenging issues in direct methanol fuel cells (DMFCs) over the decades. In this work, a composite electrochemical catalyst of Pd-coupled Ag and ZnO for the possible replacement of expensive Pt catalysts in DMFCs is successfully prepared. The as-made Pd@Ag/ZnO exhibits specific activity, which is 1.8-fold, 2.8-fold, and 4.6-fold higher than that of a Pd/ZnO catalyst, 20% Pd/C catalyst and Pd black, respectively. The improvement of the catalytic mechanism is likely due to the synergistic interaction between Pd@Ag and ZnO. The density functional theory (DFT) calculation results confirm that Ag doped into Pd weakens the adsorption of CO, dramatically improving the capability to resist CO poisoning.